A temperature gradient-induced directional growth of a perovskite film. Issue 33 (5th August 2020) - Hao, Lianzheng; Li, Zhipeng; Wang, Li; Liu, Ranran; Shao, Zhipeng; Zhou, Zhongmin; Guo, Xin; Cui, Guanglei; Liu, Shengzhong Frank; Pang, Shuping
Abstract : A temperature gradient was constructed in the MA gas healing method to realize directional growth of the perovskite films. Abstract : The directional growth of a solution-processed perovskite film is critical for its photovoltaic performance. The conventional solvent evaporation-induced film growth is nearly a top-down growth process normally with void defects at the bottom interface due to the volume shrinkage. Herein, based on the fast degassing behaviour of the methylamine gas from the perovskite film, an instantaneous bottom-up temperature gradient is constructed to regulate the growth direction. It is found that such temperature gradient could induce a bottom-up growth of the perovskite film with close contact to the bottom layer, resulting in the reduced defects in the perovskite film and the improved carrier injection efficiency into the electron selective layer. The device efficiency based on a pure MAPbI3 perovskite is significantly enhanced from 16.14% to 20.16%. The finding in this study highly indicates the importance of the directional growth of perovskite thin films for the highly efficient perovskite solar cells.